2013
DOI: 10.1103/physrevlett.110.086105
|View full text |Cite
|
Sign up to set email alerts
|

Local Atomic Order in the Melt and Solid-Liquid Interface Effect on the Growth Kinetics in a Metallic Alloy Model

Abstract: We illustrate for a solid-liquid interface how local atomic order in a metallic melt (NiZr) transforms into a massive in-plane ordering at the surface of a crystal (bcc Zr) when commensurability is given between the solute-centered clusters of the melt and the periodic potential of the crystalline surface for a given orientation. Linking molecular dynamics simulation to phase-field modeling allows us to estimate quantitatively the influence of the surface effect on the growth kinetics. This study sheds new lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…As for the case of classical systems [28], we find that this tendency to noncrystalline order increases with the degree of supercooling. If a correlation between local order and crystal deposition rate could be established, then a difference in the packing efficiency for the two isotopic species as revealed by our structural analysis might provide a physical basis to explain the observed dependence of the crystal growth rate on the oD 2 mole fraction; the rearrangement of local noncrystalline structures in the supercooled melt at the liquid/crystal interface would tend to lower the particle diffusivity, thus slowing down the crystal growth [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As for the case of classical systems [28], we find that this tendency to noncrystalline order increases with the degree of supercooling. If a correlation between local order and crystal deposition rate could be established, then a difference in the packing efficiency for the two isotopic species as revealed by our structural analysis might provide a physical basis to explain the observed dependence of the crystal growth rate on the oD 2 mole fraction; the rearrangement of local noncrystalline structures in the supercooled melt at the liquid/crystal interface would tend to lower the particle diffusivity, thus slowing down the crystal growth [5].…”
mentioning
confidence: 99%
“…Understanding the stability of supercooled liquids with respect to crystallization is a fundamental open problem in condensed matter physics [1]. In this regard, since crystallization competes with glass formation, a knowledge of the mechanisms that govern the crystal growth in supercooled liquids is considered an important step to elucidate the nature of the glass transition [2][3][4][5][6]. So far, experimental studies aiming at providing microscopic insights into the dynamics and crystallization of supercooled liquids have been largely based on the use of colloidal suspensions [7,8], where the large particle size allows one to follow the crystal growth on the laboratory time scale.…”
mentioning
confidence: 99%
“…24 molecular dynamics simulation studies of crystal growth in supercooled binary alloys have demonstrated the importance of structural ordering in the liquid near the liquid-crystal interface in determining the crystal growth rate. 4,29 The extent to which such findings could be relevant to the interpretation of the effects of mixing reported here for quantum binary mixtures represents, however, an open and interesting question that deserves further work. As a final comment, we note that a possible competition between the hcp and fcc structures, as suggested by our experimental data (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As we will only use these reduced variables, we omit the tildes. For the soft sphere model [27] we apply U (r) = 4ε(σ/r) 12 . For simulations, we have considered the system of N = 30000 particles that were simulated under periodic boundary conditions mostly in the Nose-Hover (NVT) and also in NPT ensambles.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…The computer simulation of local order is the high precision method that allows to detect subtle changes between slightly different states of the particle system [9][10][11][12] and uncover effects lately accessible to real experiment [13]. Recently the local structure physics brought together simulations and experiment in the nanoplasmonic, quantum optics, soft condensed matter and quantum spectroscopy [13][14][15][16].…”
mentioning
confidence: 99%